2015
DOI: 10.1111/bcp.12615
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate drug use in older people: a nationwide comparison of different explicit criteria for population‐based estimates

Abstract: AIMSThe aim was to investigate the prevalence of potentially inappropriate medication use among older people in Sweden according to five different published sets of explicit criteria from Europe and the US. METHODSThis was a nationwide cross-sectional, register-based study across the whole of Sweden in 2008. All individuals aged 65 years and older were included (n = 1 346 709, both community-dwelling and institutionalized persons). We applied all drug-specific criteria included in the 2012 Beers Criteria, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 60 publications
8
74
3
2
Order By: Relevance
“…Poly-pharmacy has been shown in several studies to be associated with PIMs [14][15][16]. Furthermore, our findings that females have 0.4 PIM more than males is consistent with other studies, a fact that deserves further investigation [17][18][19][20][21]. While neither socioeconomic status nor comorbidity explained sex differences in one study, biological and social factors were suggested to play a role by some investigators [19,21].…”
Section: Discussionsupporting
confidence: 91%
“…Poly-pharmacy has been shown in several studies to be associated with PIMs [14][15][16]. Furthermore, our findings that females have 0.4 PIM more than males is consistent with other studies, a fact that deserves further investigation [17][18][19][20][21]. While neither socioeconomic status nor comorbidity explained sex differences in one study, biological and social factors were suggested to play a role by some investigators [19,21].…”
Section: Discussionsupporting
confidence: 91%
“…LILACS, PubMed, Scopus, and the Web of Science databases were reviewed (through June 2013) to identify observational studies that evaluated the association between potentially inappropriate drug therapy for the elderly and relevant risk factors (age, gender, and polypharmacy). Age, gender, and polypharmacy variables were chosen, as in the literature, because they are frequently associated with a higher incidence of PIDT in local studies (no multicenter) [15,18]. Despite variables, gender and age, cannot be changed, they can set more susceptible groups to the use of PIDT, which can generate red flags in clinical practice.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacovigilance pertains to the detection, assessment, understanding and prevention of adverse effects or any other drug-related problem [Morin et al 2015] with the aim of enhancing medication safety and patient care. E-pharmacovigilance (where a computer links a patient's medications with their laboratory results) can inform prescribers of potential ADRs in the setting of abnormal laboratory values [Neubert et al 2013].…”
Section: Adr Prediction Toolsmentioning
confidence: 99%